Efficiency of Using Macrolophus nubilus H.S. for Protecting Tomatoes from Major Pests in the Greenhouse Conditions of South Kazakhstan - Ainur Alimbekova; Abai Sagitov; Bakhytzhan Duisembekov; Aizhan Chadinova; Karlygash Alpysbayeva (AGRIVITA, Journal of Agricultural Science, 2021)
Since 2015, the greatest harm to greenhouse vegetables in Kazakhstan has been caused by a previously unknown pest of nightshades – the South American tomato moth (Tuta absoluta) and the greenhouse whitefly (Trialeurodes vaporariorum). To obtain an environmentally friendly product, for the first time in Kazakhstan, the biological features of the predatory bug Macrolophus nubilus were studied and a complex integrated system was developed using biological methods. The data obtained on the survival rate and duration of development of M. nubilus larvae indicate that the eggs of the Sitotroga cerealella, as well as the eggs and larvae of the T. vaporariorum and T. absoluta, serve as a complete food for the predatory bug. Production tests of M. nubilus to assess the effect of temperature and photoperiod on the duration of larval development were carried out in the greenhouse complex “Naimbekov” on an area of 1 hectare (early indeterminate tomato hybrid Attia F1). The assessment of the biological effectiveness of M. nubilus against T. vaporariorum and T. absoluta was carried out in the greenhouse complex “Adelya” on an area of 5 hectares (mediumfruited carpal tomato hybrid Merlis F1) in southern Kazakhstan. These results contribute to more sustainable tomato production.